MACROSEISMIC EFFECT OF THE EARTHQUAKE OCCURRED ON 03.02.2015 AT THE BORDER OF POLTAVA AND SUMY REGIONS - Chalyi, O.; Il'enko, V.; Scherbina, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of the study of macroseismic effect of the earthquake on the area of Sumy and Poltava regions, occurred on 3 February 2015 at 07 hours 56 min. local time are represented. It is charecterizwed by magnitude of M = 4.6 with instrumental geographical latitude and longitude: 50.64oN and 34.13oE respectively. The aim of this paper is studying the nature of the earthquake occurrence as well as the source parameters and local patterns of attenuation of energy seismic shaking on the base of the spatial distribution of instrumental and macroseismic effectdata of this earthquake. This study is needed to predict the magnitude and intensity of the possible future earthquakes. Methods. Seismotectonic setting within the area of earthquake is analyzed. Records of seismic oscilations registered on seismic stations in Ukraine and global seismic network are processed. Their spectrograms are analyzed. For studying the distribution of seismic effects on the land surface macroseismic survey are organized in order to estimate consequences of this earthquake. By visual observation and analysis of information obtained through public poll of population of area where the earthquake occurre, maps of macroseismic effect of this seismic event were made. Results. The analysis of materials of field observations and population poll, maps of earthquake effect on the area of Sumy and Poltava regions were made. This maps indicate 6 degree seismic intensity was observed in the earthquake focus. It is found that a second shock occurred after the first one in a second, which also had an impulse nature. The second shock was of much greater intensity. The quake was sensed by people in open territory. As a result from such kind of shakings unfixed objects fell down. Many buildings located at the epicenter in shows presence of cracks in the plaster. Most water reservoirs show hight fluctuation of water level. The earthquake occurred in the area of 50 km in radius from macroseismic epicenter. Maximum intensity was observed in villages Timophyivka, Bakuty and Plishyvets. Determined macroseismic parameters of the earthquake occurred to be slightly different from the instrumentally established – macroseismic latitude and longitude: 50.49°N and 34.22°E respectively. Possible interpreattion of the differences observed and mechanism of rupture of medium continuity at the studied earthquake are made. Scientific innovation. For the first time on the the areqa Dnieper-Donets Depression (DDD) six degree tectonic earthquake is investigated with complex of instrumental methods and macroseismic survey. Macroseismic parameters of its source were established and maps of the distribution of macroseismic intensity fluctuations were made. It is shown that in the epicenter of the earthquake occurred on 3 February 2015, where soils is related to second category by seismic properties, were observed seismic impacts that match the intensity shown in the maps of general seismic zoning GSZ-2004-S. These maps of general seismic zoning are the part of Department building standards DBS -V.1.1: 12-2014 "Construction in seismic regions of Ukraine". The practical significance. The results of investigation will be used to make possible prediction about magnitude and intensity of future earthquakes that might be in the area of DDD and to provide seismic protection for the population and important industrial objects.